Nano silicon carbide particle and preparation method thereof

By using an external electric field to cause Joule thermal response on the conductive substrate, the precursor polycarbosilane is pyrolyzed into ceramic, and the problems of complex, dangerous, time-consuming and energy-consuming preparation of silicon carbide nanoparticles in the prior art are solved, and a fast, efficient and safe preparation method is achieved, and the adjustability of particle size is improved.

CN119822373APending Publication Date: 2025-04-15INST OF CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510195122.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing methods for preparing silicon carbide nanoparticles have problems such as complex production process, dangerous, time-consuming and energy-consuming, expensive equipment and poor particle size adjustment.

Method used

By mixing the precursor polymer polycarbosilane with an organic solvent, place it on a conductive substrate, removing the organic solvent, using an external electric field to generate a Joule thermal response, pyrolyzed and ceramicized the precursor polycarbosilane to generate nano-silicon carbide particles.

Benefits of technology

A fast and efficient preparation process is achieved, energy consumption and production costs are reduced, safety and particle size adjustment are improved, and the resulting silicon carbide particles are regular in shape, smooth in surface and few defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822373A_ABST
    Figure CN119822373A_ABST
Patent Text Reader

Abstract

The invention relates to nano silicon carbide particles and a preparation method thereof, belongs to the field of ceramic powder and nano materials, and solves at least one of the problems of complicated production process, low preparation efficiency, harsh reaction conditions, higher cost and poor size adjustability of the existing method for preparing the silicon carbide particles and the obtained silicon carbide particles. The preparation method comprises the following steps: mixing a precursor polymer polycarbosilane with an organic solvent to obtain a precursor polycarbosilane solution; placing the precursor polycarbosilane solution on a conductive substrate to obtain a polycarbosilane-conductive substrate complex; externally applying an electric field to a conductive substrate in the polycarbosilane-conductive substrate complex to obtain a nano silicon carbide-conductive substrate complex; and separating the nano silicon carbide particles from the nano silicon carbide-conductive substrate composite. The preparation method disclosed by the invention has the advantages of rapidness, high efficiency and the like, the size of the obtained silicon carbide particles is nanoscale, and the adjustability of the size is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic powder and nano material, and in particular to nano silicon carbide particles and a preparation method thereof. Background Art

[0002] Silicon carbide (SiC) ceramic nanoparticle materials are becoming a frontier hotspot in materials science research due to their special physical properties at the nanoscale, such as excellent optical, electrical and mechanical properties, especially in the fields of high-performance electronic devices, advanced mechanical components and new energy materials, showing significant market potential and technological advantages.

[0003] The commonly used methods for preparing silicon carbide nanoparticles that have been reported so far include carbon thermal reduction, high-energy ball milling, laser or chemical etching, combustion reaction synthesis, sol-gel method, vapor deposition method, precursor conversion method, etc.; for example, (a) a carbon source (such as carbon black, graphite, etc.) and a silicon source (such as silicon dioxide, silicon powder, etc.) are mixed in a certain proportion, the mixture is placed in a high-temperature furnace, and heated to 1500-2000°C under the protection of an inert gas (such as argon). At high temperatures, the carbon reacts with the silicon source to generate nano-silicon carbide particles; (b) SiC is etched in a mixed electrolyte of hydrofluoric acid and nitric acid to obtain SiC nanocrystals; (c) SiC ceramic targets are ablated at high temperatures generated by lasers to make them It decomposes and forms nanoparticles; (d) An organic precursor containing silicon and carbon (such as polycarbosilane or silanol) is hydrolyzed and condensed in a solvent to form a sol, which is then converted into silicon carbide by drying and pyrolysis; (e) A gaseous precursor (such as silane and methane) is introduced into a reaction chamber, decomposed and deposited at high temperature to form silicon carbide; (f) SiC nanoparticles are synthesized by explosive explosion in an inert and closed environment using the precursor polycarbosilane as a raw material; (g) SiC micro-nanoparticles are prepared by Joule flash heating using Si powder, SiO2 powder and various carbon powders as raw materials; (h) Micron-sized SiC particles are used as raw materials and high-energy ball milling is used to crush the micron-sized SiC particles into SiC nanoparticles.

[0004] The above existing preparation methods generally have problems such as complex production process, dangerous process, time-consuming and energy-consuming, expensive equipment, and poor adjustability of particle size. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a nano-silicon carbide particle and a preparation method thereof, so as to solve at least one of the following technical problems existing in the existing method for preparing silicon carbide particles and the obtained silicon carbide particles: (1) the production process is complicated and the preparation efficiency is low; (2) the reaction conditions are harsh, resulting in a dangerous process and high energy consumption; (3) the equipment is expensive and the cost is high; (4) the size adjustability of silicon carbide particles is poor.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing nano silicon carbide particles, comprising the following steps:

[0008] Step S1, under an inert atmosphere, mixing a precursor polymer polycarbosilane with an organic solvent to obtain a precursor polycarbosilane solution with a concentration c of 0.1-100 mg / mL;

[0009] Step S2, placing a precursor polycarbosilane solution on a conductive substrate, removing the organic solvent, and obtaining a polycarbosilane-conductive substrate composite;

[0010] Step S3, applying an electric field to the conductive substrate in the polycarbosilane-conductive substrate composite under vacuum or inert atmosphere, so that the polycarbosilane on the conductive substrate is thermally decomposed and undergoes a ceramic transformation to obtain a nano-silicon carbide-conductive substrate composite;

[0011] Step S4, separating nano-silicon carbide particles from the nano-silicon carbide-conductive substrate composite.

[0012] Further, in step S3, the external electric field is provided by a DC power supply; the input current I is 10-200A; and / or the input voltage V is 10-380V; and / or the electric work duration t is 10ms-10min.

[0013] Further, the heating rate R of the conductive substrate is determined based on the relationship (1):

[0014] (I×V)÷A=k×R(1)

[0015] Where A is the area of ​​the conductive substrate in cm 2 ; k is a proportional coefficient related to the material of the conductive substrate and the content of the precursor polycarbosilane attached to the conductive substrate, and the value range of k is 0.015-0.09; I is the input current, in amperes; V is the input voltage, in volts.

[0016] Furthermore, in step S3, the heating rate R of the conductive substrate is 1000-20000° C. / s.

[0017] Furthermore, in steps S1 and S3, nano-silicon carbide particles meeting the target size range are obtained by regulating the concentration c of the precursor polycarbosilane solution, the heating rate R of the conductive substrate, and the duration t of the electrical treatment.

[0018] Furthermore, the concentration c of the precursor polycarbosilane solution, the heating rate R of the conductive substrate, the duration t of the electrical treatment, and the target size range have one of the following characteristics:

[0019] (e) c = 0.1-0.2 mg / mL, R = 18000-20000 °C / s, t = 100-200 ms, target size range 10-50 nm;

[0020] (f) c = 0.8-5.5 mg / mL, R = 10000-16000 °C / s, t = 0.8-2.0 s, target size range 50-250 nm;

[0021] (g) c = 6.0-8.0 mg / mL, R = 10000-16000 °C / s, t = 1.0-2.0 s, target size range 250-400 nm;

[0022] (h) c = 8.5-10.0 mg / mL, R = 1000-5000 °C / s, t = 4.0-8.0 s, target size range 400-500 nm.

[0023] Furthermore, the conductive substrate includes a carbon-based material and a metal-based material; the carbon-based material includes at least one of carbon fiber fabric, carbon paper, and carbon foil; the metal-based material includes at least one of copper foil, copper sheet, silver foil, and silver sheet; wherein the fiber diameter of the carbon fiber braid is 0.1-10 μm.

[0024] Furthermore, the specific steps of step S4 include: placing the nano-silicon carbide-conductive substrate composite in a liquid dispersant, using ultrasonic treatment to separate the nano-silicon carbide from the conductive substrate and disperse it in the liquid dispersant; and then removing the liquid dispersant through vacuum drying to obtain nano-silicon carbide particles.

[0025] Furthermore, in step S4, the ultrasonic treatment time is 10-60 min, the power is 200-1000 W; the vacuum drying temperature is 30-100° C., the time is 10-60 min, and the vacuum degree is 100-1000 Pa.

[0026] The present invention provides a nano silicon carbide particle, and the nano silicon carbide particle is obtained by the preparation method as described above.

[0027] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0028] (1) The preparation method of the present invention has the advantages of being fast and efficient. The precursor polysilane solution is placed on a conductive substrate, and an external electric field is used to cause the conductive substrate to generate a Joule heat response. The precursor polysilane solution on the conductive substrate is pyrolyzed and ceramicized under the action of Joule heat to obtain silicon carbide particles. Compared with the existing carbon thermal reduction method, etching method, etc., the production cycle is shorter and the preparation efficiency is higher.

[0029] (2) The preparation method of the present invention has the advantages of mild reaction conditions, high safety and low energy consumption. The method does not need to perform complex reactions at high temperatures like the traditional carbon thermal reduction method, nor does it need to use high temperature and high pressure reaction conditions like the chemical vapor deposition method. By applying an external electric field to make the conductive substrate produce Joule heat response, the pyrolysis and ceramicization of the precursor polysilane solution can be achieved under relatively mild conditions. Since there is no need to use dangerous factors such as high-temperature flames and high-pressure gases, the entire preparation process is safer and more reliable. Compared with methods with potential safety hazards such as laser etching, combustion reaction synthesis, and precursor polycarbosilane + explosive explosion, the Joule heat response method does not produce dangerous situations such as high-temperature radiation and high-pressure explosion during operation, greatly reducing the safety risks in the production process. The method of preparing silicon carbide nanoparticles by using an external electric field to make the conductive substrate produce Joule heat response has the advantages of lower energy consumption through rapid heating and high energy conversion efficiency compared with traditional carbon thermal reduction methods, high-energy ball milling methods, etc.

[0030] (3) The preparation method of the present invention has the advantages of low equipment cost and cost. Traditional methods for preparing silicon carbide nanoparticles, such as chemical vapor deposition, combustion reaction synthesis, laser etching, etc., often require the use of complex high-temperature reactors, high-voltage equipment, high-power lasers, etc., which are expensive. The method of the present invention does not require these complex and expensive equipment, but only requires a simple conductive substrate and an external electric field device, which greatly reduces the equipment cost and overall cost.

[0031] (4) The preparation method of the present invention has the advantage that the size of silicon carbide particles can be adjusted. By controlling the concentration of the precursor polymer solution and the parameters of the applied electric field to achieve a synergistic effect, silicon carbide particles within the expected target particle size range can be obtained. Traditional methods for preparing silicon carbide nanoparticles, such as high-energy ball milling and precursor conversion methods, are often difficult to accurately control the particle size, and the morphology and uniformity of the particles are not ideal. The present invention can achieve the regulation of silicon carbide particle size and meet the requirements of different applications for particle size. The prepared silicon carbide particles have a regular morphology, a smooth surface, and few defects, which can better meet the application requirements of high-performance materials.

[0032] (5) In some preferred embodiments, the particle size controllability and uniformity can be better achieved by precisely controlling the concentration of the polycarbosilane solution. By selecting appropriate parameters of the applied electric field, the required appropriate heating rate can be provided, and the appropriate duration of the electric power can be matched, thereby providing appropriate Joule heat for the polycarbosilane on the conductive substrate, saving time and reducing energy consumption, while helping to obtain more uniform silicon carbide particles, further improving the particle size controllability and quality of the silicon carbide particles.

[0033] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0035] Figure 1 This is the XRD spectrum of SiC nanoparticles prepared by the reaction of Example 6 of the present invention;

[0036] Figure 2 This is a SEM photo of SiC nanoparticles prepared by the reaction of Example 6 of the present invention;

[0037] Figure 3 This is a TEM photo of SiC nanoparticles prepared by the reaction of Example 6 of the present invention;

[0038] Figure 4 This is a SEM photo of the nano-silicon carbide-carbon fiber fabric composite obtained in Example 6 of the present invention;

[0039] Figure 5 This is the XRD spectrum of SiC nanoparticles prepared by the reaction of Example 8 of the present invention;

[0040] Figure 6 This is a SEM photograph of SiC nanoparticles prepared by the reaction of Example 8 of the present invention. DETAILED DESCRIPTION

[0041] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0042] In view of the above-mentioned problems existing in the existing methods for preparing nano-silicon carbide particles and the obtained silicon carbide particles, it is urgent to develop a new preparation method to overcome the limitations of the existing methods, improve the preparation efficiency of silicon carbide nanoparticles, reduce production costs, reduce energy consumption, improve the safety of the preparation process, and make the prepared silicon carbide particles have nanoscale and adjustable size.

[0043] Based on this, in a first aspect, the present invention provides a method for preparing nano silicon carbide particles, comprising the following steps:

[0044] Step S1, under an inert atmosphere, mixing a precursor polymer polycarbosilane with an organic solvent to obtain a precursor polycarbosilane solution with a concentration c of 0.1-100 mg / mL;

[0045] Step S2, placing a precursor polycarbosilane solution on a conductive substrate, removing the organic solvent, and obtaining a polycarbosilane-conductive substrate composite;

[0046] Step S3, applying an electric field to the conductive substrate in the polycarbosilane-conductive substrate composite under vacuum or inert atmosphere, so that the polycarbosilane on the conductive substrate is thermally decomposed and undergoes a ceramic transformation to obtain a nano-silicon carbide-conductive substrate composite;

[0047] Step S4, separating nano-silicon carbide particles from the nano-silicon carbide-conductive substrate composite.

[0048] Compared with the prior art, the preparation method of the present invention has the advantages of being fast and efficient. By placing a precursor polysilane solution on a conductive substrate, an external electric field is used to cause the conductive substrate to generate a Joule heat response, thereby causing the precursor polysilane solution attached to the conductive substrate to pyrolyze and ceramicize under the action of Joule heat to obtain silicon carbide particles. Compared with the existing carbon thermal reduction method, etching method, etc., the production cycle is shorter and the preparation efficiency is higher.

[0049] The preparation method of the present invention has the advantages of mild reaction conditions, high safety and low energy consumption. The method does not need to perform complex reactions at high temperatures like the traditional carbon thermal reduction method, nor does it need to use high temperature and high pressure reaction conditions like the chemical vapor deposition method. The conductive substrate is made to produce Joule heat response by an external electric field, and the pyrolysis ceramicization of the precursor polysilane solution can be achieved under relatively mild conditions. Since there is no need to use dangerous factors such as high-temperature flames and high-pressure gases, the entire preparation process is safer and more reliable. Compared with the methods with potential safety hazards such as laser etching, combustion reaction synthesis, and precursor polycarbosilane + explosive explosion, the Joule heat response method does not produce dangerous situations such as high-temperature radiation and high-pressure explosion during operation, greatly reducing the safety risks in the production process. The present invention utilizes an external electric field to make the conductive substrate produce Joule heat response to prepare a method for silicon carbide nanoparticles, which has the advantages of lower energy consumption by rapid heating and high energy conversion efficiency compared to traditional carbon thermal reduction, high-energy ball milling, etc.

[0050] The preparation method of the present invention has the advantages of low equipment cost and cost. Traditional methods for preparing silicon carbide nanoparticles, such as chemical vapor deposition, combustion reaction synthesis, laser etching, etc., often require the use of complex high-temperature reactors, high-voltage equipment, high-power lasers, etc., which are expensive. The method of the present invention does not require these complex and expensive equipment, but only requires a simple conductive substrate and an external electric field device, which greatly reduces the equipment cost and overall cost.

[0051] The preparation method of the present invention has the advantage that the size of silicon carbide particles can be adjusted. By controlling the concentration of the precursor polymer solution and the parameters of the applied electric field to achieve a synergistic effect, silicon carbide particles within the expected target particle size range can be obtained. Traditional methods for preparing silicon carbide nanoparticles, such as high-energy ball milling and precursor conversion methods, are often difficult to accurately control the particle size, and the morphology and uniformity of the particles are not ideal. The present invention can achieve accurate regulation of the size of silicon carbide particles to meet the requirements of different applications for particle size. The prepared silicon carbide particles have a regular morphology, a smooth surface, and few defects, and can better meet the application requirements of high-performance materials.

[0052] It can be seen that the preparation method of the present invention has the advantages of being fast, efficient, having mild reaction conditions, and having low cost. The size of the obtained silicon carbide particles is at the nanoscale, achieving size adjustability.

[0053] It should be noted that in the present invention, the size of the final obtained nano silicon carbide particles is greatly affected by the concentration c of the precursor polycarbosilane solution described in step S1. In addition, the parameters (such as voltage, current, electric work duration, etc.) of the external electric field can be adjusted to accurately control the generation and transfer of Joule heat, and further regulate the growth process of the particles and the final size and quality. Through this coordinated regulation, the present invention can prepare silicon carbide particles within the expected target particle size range, with significant size adjustability and morphology controllability. For example, by adjusting the concentration c of the precursor polycarbosilane solution, the deposition amount of the precursor polycarbosilane on the conductive substrate can be controlled, thereby affecting the size of the final silicon carbide particles. Appropriate concentration c helps to form a uniform precursor deposition layer, reduce defects in the deposition layer, and thus generate silicon carbide particles with uniform size, regular morphology, and smooth surface under the action of appropriate Joule heat.

[0054] Exemplarily, the concentration c of the precursor polycarbosilane solution is 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2.0 mg / mL, 2.5 mg / mL, 3.0 mg / mL, 3.5 mg / mL, 4.0 mg / mL, 5.0 mg / mL, 6.5 mg / mL, 7.5 mg / mL, 9.0 mg / mL, 15 mg / mL, 25 mg / mL, 40 mg / mL, 55 mg / mL, 70 mg / mL, 85 mg / mL. The concentration c here refers to the ratio of the mass of the precursor polycarbosilane to the volume of the organic solvent.

[0055] Preferably, the concentration c of the precursor polycarbosilane solution is 0.1-20 mg / mL; further, c is 0.1-10 mg / mL.

[0056] Specifically, in step S1 and step S3, the inert atmosphere is nitrogen, argon, or a combination of both.

[0057] Specifically, in step S1, the precursor polymer polycarbosilane includes but is not limited to solid or liquid polycarbosilanes of various structures and molecular weights, such as perhydropolycarbosilane, vinyl polycarbosilane, allyl polycarbosilane, and the like.

[0058] In some embodiments, the number average molecular weight of the precursor polymer polycarbosilane is 800-2500 g / mol, for example, 1000 g / mol, 1500 g / mol, or 2000 g / mol.

[0059] Specifically, in step S1, the organic solvent is a solvent that can dissolve silane to form a homogeneous solution, including one or more of alkane solvents, ether solvents, ketone solvents, and aromatic solvents. The alkane solvent is selected from one or more of n-hexane, n-octane, n-decane, chloroform, dichloromethane, dichloroethylene, mineral oil, petroleum ether, etc.; the ether solvent is selected from one or more of ether, dibutyl ether, etc.; the ketone solvent is selected from one or more of acetone, methyl ethyl ketone, cyclohexanone, etc.; the aromatic solvent is selected from one or more of toluene, m-xylene, p-xylene, o-xylene, chlorobenzene, etc.

[0060] Specifically, in step S1, the precursor polymer polycarbosilane is mixed with the organic solvent by stirring, the stirring speed is 200-700r / min, the time is 1min-2h, and further, the time is 1min-30min. The above stirring speed and time range ensure uniform mixing while avoiding the problem of excessive shearing, thereby providing a good foundation for subsequent pyrolysis and ceramicization to obtain silicon carbide ceramic particles with controllable particle size and good morphology quality. Exemplarily, the stirring speed is 300r / min, 400r / min, 500r / min, 600r / min; the time is 5min, 10min, 15min, 20min, 25min.

[0061] Specifically, in step S2, the conductive substrate includes a carbon-based material and a metal-based material; the carbon-based material includes at least one of carbon fiber fabric, carbon paper, and carbon foil; the metal-based material includes at least one of copper foil, copper sheet, silver foil, and silver sheet; wherein the fiber diameter of the carbon fiber fabric is 0.1-10 μm. The use of the above-mentioned moderate carbon fiber diameter can ensure the uniform adhesion of the precursor polycarbosilane on the fiber surface, improve the uniformity and quality of the silicon carbide particles after pyrolysis ceramicization, and facilitate the controllability of the particle size. Exemplarily, the fiber diameter of the carbon fiber fabric is 0.5 μm, 1.0 μm, 2.0 μm, 5.0 μm, and 8.0 μm.

[0062] Specifically, in step S2, the precursor polycarbosilane solution is placed on the conductive substrate by immersion or dripping. For example, the conductive substrate is completely immersed in the precursor polycarbosilane solution to ensure that each part of the conductive substrate is fully in contact with the solution, which is suitable for a conductive substrate with a larger area; or, the precursor polycarbosilane solution is dripped onto the conductive substrate, which is suitable for a conductive substrate with a smaller area; for the dripping method, the dripping amount is 0.01-0.05 ml / cm 2 , so as to form a uniform and moderate solution distribution on the conductive substrate, and under the action of a suitable external electric field, more uniform nano-SiC particles with better morphology and quality can be obtained. For example, the amount of dripping is 0.02 ml / cm 2 、0.03ml / cm 2 、0.04ml / cm 2 .

[0063] Specifically, in step S2, the precursor polycarbosilane solution is placed on a conductive substrate, and then the organic solvent is removed in a vacuum environment by vacuum treatment, for example, by vacuum evaporation or vacuum distillation, and commonly used equipment includes a rotary vacuum evaporator, a vacuum distillation device, a vacuum drying oven, a vacuum concentrator, and a vacuum solvent recovery system.

[0064] In some embodiments, the vacuum degree of the vacuum environment is 100-1000Pa, and the time of the vacuum treatment is 1-60min. Preferably, the vacuum degree is 200-800Pa, and the time of the vacuum treatment is 10-30min. Within the range of the above-mentioned vacuum degree and treatment time, it is possible to ensure that the solvent is fully evaporated, and at the same time ensure that the precursor polycarbosilane after the solvent is removed is evenly distributed on the conductive substrate, so as to obtain more uniform and better-shaped nano-silicon carbide particles, which helps to achieve controllable particle size and quality improvement. Exemplarily, the vacuum degree of the vacuum environment is 300Pa, 400Pa, 500Pa, 600Pa, 700Pa, 900Pa; the time of vacuum treatment is 5min, 15min, 20min, 40min, 50min.

[0065] Specifically, in step S3, the external electric field is provided by a direct current power supply, and its parameters include input current, input voltage and electric work duration.

[0066] In some embodiments, the input current I is 10-200 A. Exemplarily, the input current I is 20 A, 40 A, 60 A, 80 A, 100 A, 120 A, 150 A, 180 A. Further, the input current I is 20 A-140 A. Further, the input current I is 40 A-120 A.

[0067] In some embodiments, the input voltage V is 10-380 V. Exemplarily, the input voltage V is 20 V, 40 V, 60 V, 90 V, 120 V, 150 V, 180 V, 220 V, 270 V, 320 V. Further, the input voltage V is 10 V-100 V. Further, the input voltage V is 20 V-50 V.

[0068] In some embodiments, the electric power duration t is 10ms-10min. Exemplarily, the electric power duration t is 50ms, 100ms, 150ms, 250ms, 0.5s, 0.75s, 1.5s, 3.0s, 6.0s, 8.0s, 24s, 48s, 1min, 2min, 5min, 8min. Further, the electric power duration t is 50ms-15s. Further, the electric power duration t is 100ms-10s.

[0069] In some embodiments, in step S3, after applying an external electric field to the conductive substrate, the heating rate R of the conductive substrate is 1000-20000°C / s. The ceramic transformation of polycarbosilane usually needs to be carried out at a higher temperature. For example, above 1200°C, polycarbosilane will gradually transform into amorphous SiC, and above 1500°C, it will further crystallize into β-SiC. Therefore, the heating rate R of the conductive substrate needs to be high enough to quickly reach the decomposition and ceramic temperature of polycarbosilane.

[0070] It can be understood that the factors affecting the heating rate mainly include input current, voltage and resistance. Among them, the resistance is affected by the material and size of the conductive substrate, as well as the content of the precursor polycarbosilane (sample) attached to the conductive substrate. Specifically, the higher the concentration of the precursor polycarbosilane solution and the larger the amount of addition, the higher the resistivity of the sample and the worse the conductivity. This is because polycarbosilane itself is an organic polymer with poor conductivity. When it is attached to the surface of the conductive substrate, it will increase the overall resistance. In addition, the larger the size of the conductive substrate, the greater the resistance.

[0071] In some preferred embodiments, the heating rate R of the conductive substrate is determined based on the relationship (1):

[0072] (I×V)÷A=k×R(1)

[0073] Where A is the area of ​​the conductive substrate in cm 2 ; k is a proportional coefficient related to the material of the conductive substrate and the content of the precursor polycarbosilane attached to the conductive substrate, and the value range of k is 0.015-0.09; I is the input current, in amperes; V is the input voltage, in volts.

[0074] The value range of k is determined by combining the material of the conductive substrate and the concentration range of polycarbosilane. In this way, when adjusting the size of the conductive substrate, the appropriate input current I and input voltage V can be quickly determined based on the above formula to achieve the required heating rate R.

[0075] Exemplarily, the inventors found that when a carbon-based material is used as a conductive substrate, within the concentration range c of the polycarbosilane of 0.1-100 mg / mL, the appropriate range of the proportionality coefficient k is 0.015-0.09. This range can be used to quickly determine the input current I and input voltage V to achieve the desired heating rate R. The proportionality coefficient here is applicable to the relationship (1), where the unit of the input current I is ampere (A), the unit of the input voltage V is volt (V), and the unit of A is cm 2 , the unit of the heating rate R is °C / s. Exemplarily, the values ​​of the proportionality coefficient k are 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.07, and 0.08.

[0076] It should be noted that the heating rate R of the conductive substrate and the duration t of the electric work need to be synergistically optimized according to the concentration of the polycarbosilane solution to achieve efficient ceramic transformation. Therefore, in steps S1 and S3, nano-silicon carbide particles meeting the target size range are obtained by regulating the concentration c of the precursor polycarbosilane solution, the heating rate R of the conductive substrate, and the duration t of the electric work treatment.

[0077] The present invention achieves the adjustability of silicon carbide particle size within the nanoscale range by controlling the heating rate R of the conductive substrate and the duration t of the electric power treatment, combined with the concentration range of the precursor polycarbosilane solution. This collaborative optimization method can effectively regulate the ceramicization process of polycarbosilane, thereby preparing nano silicon carbide particles of different target sizes. This process optimization provides a new technical means for the preparation of high-performance nano silicon carbide materials, which can better meet high-end application scenarios with strict requirements on particle size, such as: aerospace, electronic devices, optoelectronic devices, etc.

[0078] In some preferred embodiments, the concentration c of the precursor polycarbosilane solution, the heating rate R of the conductive substrate, the duration t of the electrical treatment, and the target size range have one of the following characteristics:

[0079] (a) c = 0.1-0.2 mg / mL, R = 18000-20000 °C / s, t = 100-200 ms, target size range 10-50 nm;

[0080] (b) c = 0.8-5.5 mg / mL, R = 10000-16000 °C / s, t = 0.8-2.0 s, target size range 50-250 nm;

[0081] (c) c = 6.0-8.0 mg / mL, R = 10000-16000 °C / s, t = 1.0-2.0 s, target size range 250-400 nm;

[0082] (d) c = 8.5-10.0 mg / mL, R = 1000-5000 °C / s, t = 4.0-8.0 s, target size range 400-500 nm.

[0083] In the above (b) and (c), the size range of the obtained silicon carbide nanoparticles can be further refined by more accurately controlling the concentration c of the precursor polycarbosilane solution, the heating rate R of the conductive substrate, and the duration t of the electrical treatment.

[0084] Exemplarily, c = 0.8-1.2 mg / mL, R = 10000-12000°C / s, t = 0.8-1.0 s, and the target size range is 60-140 nm.

[0085] Exemplarily, c = 1.5-2.5 mg / mL, R = 10000-12000°C / s, t = 0.8-1.0 s, and the target size range is 120-180 nm.

[0086] Exemplarily, c = 4.5-5.5 mg / mL, R = 10000-16000°C / s, t = 1.0-2.0 s, and the target size range is 160-250 nm.

[0087] Exemplarily, c = 6.0-6.8 mg / mL, R = 10000-16000°C / s, t = 1.0-2.0 s, and the target size range is 260-340 nm.

[0088] Exemplarily, c = 7.0-8.0 mg / mL, R = 10000-16000°C / s, t = 1.0-2.0 s, and the target size range is 350-400 nm.

[0089] In some embodiments, the specific steps of step S4 include: placing the nano-silicon carbide-conductive substrate composite in a liquid dispersant, using ultrasonic treatment to separate the nano-silicon carbide from the conductive substrate and disperse it in the liquid dispersant; then performing vacuum drying to remove the liquid dispersant to obtain nano-silicon carbide particles;

[0090] The ultrasonic treatment time is 10-60min, and the power is 200-1000W;

[0091] The vacuum drying is carried out at a temperature of 30-100° C., a time of 10-60 min, and a vacuum degree of 100-1000 Pa.

[0092] For example, in step S4, the ultrasonic treatment time is 20 min, 30 min, 40 min, 50 min. Further, the ultrasonic treatment time is 30-60 min. The ultrasonic treatment power is 400 W, 600 W, 800 W.

[0093] Exemplarily, in step S4, the vacuum drying temperature is 40°C, 50°C, 60°C, 70°C, 80°C, 90°C. The vacuum drying time is 20 min, 30 min, 40 min, 50 min. The vacuum degree is 400 Pa, 600 Pa, 800 Pa. Further, the vacuum drying temperature is 50-70°C, and the vacuum drying time is 30-60 min.

[0094] Illustratively, in step S4, the liquid dispersant includes one or more of deionized water, alcohol solvents, alkane solvents, ether solvents, ketone solvents, and aromatic hydrocarbon solvents.

[0095] In a second aspect, the present invention further provides a nano-silicon carbide particle, wherein the nano-silicon carbide particle is obtained by the preparation method described in the first aspect above.

[0096] In some embodiments, the nano-silicon carbide particles have one of the following characteristics:

[0097] (a) Particle size range: 10-500 nm, particle size distribution: polydispersity index (PDI) ≤ 0.2, preferably, PDI ≤ 0.1, SiC particle size distribution is relatively uniform;

[0098] (b) Crystal structure: β-SiC, β-SiC is 100%;

[0099] (c) Specific surface area: 3.5-200m 2 / g;

[0100] (d) Shape: spherical.

[0101] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and comparative examples.

[0102] Embodiment 1:

[0103] This embodiment provides a method for preparing nano-silicon carbide particles, comprising the following steps:

[0104] Step S1, under nitrogen protection, slowly drop 0.1 g of liquid perhydropolycarbosilane (structure as shown in Formula I) with a number average molecular weight of 1300 g / mol into 1000 ml of n-hexane, and stir at a speed of 700 r / min for 1 min to obtain a polycarbosilane-n-hexane solution (i.e., a precursor polycarbosilane solution) with a concentration c of 0.1 mg / mL;

[0105]

[0106] Step S2, adding a polycarbosilane-n-hexane solution dropwise onto a carbon fiber fabric having a fiber diameter of 7 μm and a size of 3 cm×3 cm, and placing the carbon fiber fabric in a vacuum environment with a vacuum degree of 1000 Pa to remove the solvent for 60 minutes to fully evaporate the solvent, thereby obtaining a polycarbosilane-carbon fiber fabric composite;

[0107] Step S3, under nitrogen protection, connecting the polycarbosilane-carbon fiber fabric composite to a DC power supply, setting the input voltage to 48V, the input current to 120A, the electric power duration to 100ms, and the heating rate to 20000°C / s, turning on the power so that the carbon fiber fabric generates Joule heat under the action of the electric field to pyrolyze and ceramicize the precursor polycarbosilane, and obtaining the SiC nanoparticle-carbon fiber fabric composite after cooling;

[0108] Step S4, placing the SiC nanoparticle-carbon fiber fabric composite in 50 mL of anhydrous ethanol, ultrasonicating the carbon fiber fabric at a power of 1000 W for 10 min, taking out the carbon fiber fabric, and vacuum drying it at 30° C. for 60 min with a vacuum degree of 100 Pa to obtain SiC nanoparticles.

[0109] Compared with Example 1, the changed parameters and test results of Examples 2-5 and Comparative Example 1 are shown in Table 1.

[0110] Table 1: Parameters and test results of embodiments and comparative examples (first group)

[0111]

[0112]

[0113] Embodiment 6:

[0114] This embodiment provides a method for preparing nano-silicon carbide particles, comprising the following steps:

[0115] Step S1, under nitrogen protection, add 0.1 g of solid polycarbosilane (structure as shown in Formula II) with a number average molecular weight of 1500 g / mol to 100 mL of dichloromethane, and stir at a speed of 200 r / min for 2 h to obtain a polycarbosilane-dichloromethane solution (i.e., a precursor polycarbosilane solution) with a concentration c of 1.0 mg / mL;

[0116]

[0117] Step S2, adding a polycarbosilane-dichloromethane solution dropwise onto a carbon fiber fabric having a fiber diameter of 10 μm and a size of 3 cm×3 cm, and placing the carbon fiber fabric in a vacuum environment with a vacuum degree of 100 Pa to remove the solvent for 1 min to fully evaporate the solvent, thereby obtaining a polycarbosilane-carbon fiber fabric composite;

[0118] Step S3, under nitrogen protection, connecting the polycarbosilane-carbon fiber fabric composite to a DC power supply, setting the input voltage to 36V, the input current to 100A, the electric power duration to 1s, and the heating rate to 10000°C / s, turning on the power so that the carbon fiber fabric generates Joule heat under the action of the electric field to pyrolyze and ceramicize the precursor polycarbosilane, and obtaining the SiC nanoparticle-carbon fiber fabric composite after cooling;

[0119] Step S4, placing the SiC nanoparticle-carbon fiber fabric composite in 50 mL of anhydrous ethanol, ultrasonicating the carbon fiber fabric at a power of 200 W for 60 min, taking out the carbon fiber fabric, and vacuum drying it at 100° C. for 10 min with a vacuum degree of 1000 Pa to obtain SiC nanoparticles.

[0120] Compared with Example 6, the changed parameters and test results of Examples 7-12 are shown in Table 2.

[0121] Table 2: Parameters and test results of the embodiment (second group)

[0122]

[0123] Embodiment 13:

[0124] This embodiment provides a method for preparing nano-silicon carbide particles, comprising the following steps:

[0125] Step S1, under nitrogen protection, add 0.6 g of liquid vinyl-containing polycarbosilane (structure as shown in Formula III) with a number average molecular weight of 1400 g / mol to 100 mL of dichloromethane, and stir at a speed of 500 r / min for 15 min to obtain a polycarbosilane-dichloromethane solution (i.e., a precursor polycarbosilane solution) with a concentration c of 6.0 mg / mL;

[0126]

[0127] Step S2, soaking a carbon paper with a size of 3 cm×3 cm in a polycarbosilane-dichloromethane solution, and placing the carbon paper in a vacuum environment with a vacuum degree of 400 Pa to remove the solvent for 20 minutes to fully evaporate the solvent, thereby obtaining a polycarbosilane-carbon paper composite;

[0128] Step S3, under nitrogen protection, connecting the polycarbosilane-carbon paper composite to a DC power supply, setting the input voltage to 36V, the input current to 120A, the electric power duration to 1s, and the heating rate to 10000°C / s, turning on the power to allow the carbon paper to generate Joule heat under the action of the electric field to pyrolyze and ceramicize the precursor polycarbosilane, and obtaining the SiC nanoparticle-carbon paper composite after cooling;

[0129] Step S4, placing the SiC nanoparticle-carbon paper composite in 50 mL of anhydrous ethanol, ultrasonicating at a power of 600 W for 50 min, taking out the carbon paper, and vacuum drying at 60° C. for 30 min with a vacuum degree of 500 Pa to obtain SiC nanoparticles.

[0130] Compared with Example 13, the changed parameters and test results of Examples 14-18 are shown in Table 3.

[0131] Table 3: Parameters and test results of the embodiment (third group)

[0132]

[0133] Embodiment 19:

[0134] This embodiment provides a method for preparing nano-silicon carbide particles, comprising the following steps:

[0135] Step S1, under nitrogen protection, add 1.0 g of liquid perhydropolycarbosilane (structure as shown in Formula I) with a number average molecular weight of 1300 g / mol to 100 mL of tetrahydrofuran, and stir at a speed of 300 r / min for 20 min to obtain a polycarbosilane-tetrahydrofuran solution (i.e., a precursor polycarbosilane solution) with a concentration c of 10.0 mg / mL;

[0136] Step S2, soaking a carbon paper with a size of 3 cm×3 cm in a polycarbosilane-tetrahydrofuran solution, and placing the carbon paper in a vacuum environment with a vacuum degree of 600 Pa to remove the solvent for 40 minutes to fully evaporate the solvent, thereby obtaining a polycarbosilane-carbon paper composite;

[0137] Step S3, under nitrogen protection, connecting the polycarbosilane-carbon paper composite to a DC power supply, setting the input voltage to 20V, the input current to 40A, the electric power duration to 5s, and the heating rate to 1000°C / s, turning on the power to allow the carbon paper to generate Joule heat under the action of the electric field to pyrolyze and ceramicize the precursor polycarbosilane, and obtaining the SiC nanoparticle-carbon paper composite after cooling;

[0138] Step S4, placing the SiC nanoparticle-carbon paper composite in 50 mL of deionized water, ultrasonicating it at a power of 800 W for 30 min, taking out the carbon paper, and vacuum drying it at 80° C. for 50 min with a vacuum degree of 400 Pa to obtain SiC nanoparticles.

[0139] Compared with Example 19, the changed parameters and test results of Examples 20-27 and Comparative Example 2 are shown in Table 4.

[0140] Table 4: Parameters and test results of embodiments and comparative examples (fourth group)

[0141]

[0142] It can be seen from Tables 1 to 4 above that the embodiments of the present invention can quickly and efficiently prepare nano-sized silicon carbide particles under relatively mild conditions. Figure 1 and Figure 5 By controlling the concentration of the precursor polycarbosilane solution and the process parameters of the applied electric field to achieve their synergistic effect, the particle size of the silicon carbide particles can be adjusted within the nanoscale, the PDI index can be controlled at 0.1 or below, and the particle size of the obtained silicon carbide particles is relatively uniform.

[0143] In addition, if Figure 2 , Figure 4 , Figure 6 The particle size of the silicon carbide particles obtained in the embodiment of the present invention is in the nanometer scale, the particle morphology is regular, the surface is smooth, and there are few defects.

[0144] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing nano silicon carbide particles, characterized in that: The following steps are involved: Step S1, under an inert atmosphere, mixing a precursor polymer polycarbosilane with an organic solvent to obtain a precursor polycarbosilane solution with a concentration c of 0.1-100 mg / mL; Step S2, placing a precursor polycarbosilane solution on a conductive substrate, removing the organic solvent, and obtaining a polycarbosilane-conductive substrate composite; Step S3, applying an electric field to the conductive substrate in the polycarbosilane-conductive substrate composite under vacuum or inert atmosphere, so that the polycarbosilane on the conductive substrate is thermally decomposed and undergoes a ceramic transformation to obtain a nano-silicon carbide-conductive substrate composite; Step S4, separating nano-silicon carbide particles from the nano-silicon carbide-conductive substrate composite.

2. The preparation method according to claim 1, characterized in that: In step S3, the external electric field is provided by a DC power supply; the input current I is 10-200A; and / or the input voltage V is 10-380V; and / or the electric work duration t is 10ms-10min.

3. The preparation method according to claim 2, characterized in that: The heating rate R of the conductive substrate is determined based on the relationship (1): (I×V)÷A=k×R (1) Where A is the area of ​​the conductive substrate in cm 2 ; k is a proportional coefficient related to the material of the conductive substrate and the content of the precursor polycarbosilane attached to the conductive substrate, and the value range of k is 0.015-0.09; I is the input current, in amperes; V is the input voltage, in volts.

4. The preparation method according to claim 3, characterized in that: In step S3, the heating rate R of the conductive substrate is 1000-20000°C / s.

5. The preparation method according to claim 3, characterized in that: In steps S1 and S3, nano-silicon carbide particles meeting the target size range are obtained by regulating the concentration c of the precursor polycarbosilane solution, the heating rate R of the conductive substrate, and the duration t of the electrical treatment.

6. The preparation method according to claim 5, characterized in that: The concentration c of the precursor polycarbosilane solution, the heating rate R of the conductive substrate, the duration t of the electrical treatment and the target size range have one of the following characteristics: (a) c = 0.1-0.2 mg / mL, R = 18000-20000 °C / s, t = 100-200 ms, target size range 10-50 nm; (b) c = 0.8-5.5 mg / mL, R = 10000-16000 °C / s, t = 0.8-2.0 s, target size range 50-250 nm; (c) c = 6.0-8.0 mg / mL, R = 10000-16000 °C / s, t = 1.0-2.0 s, target size range 250-400 nm; (d) c = 8.5-10.0 mg / mL, R = 1000-5000 °C / s, t = 4.0-8.0 s, target size range 400-500 nm.

7. The preparation method according to claim 1, characterized in that: The conductive substrate includes a carbon-based material and a metal-based material; the carbon-based material includes at least one of carbon fiber fabric, carbon paper, and carbon foil; the metal-based material includes at least one of copper foil, copper sheet, silver foil, and silver sheet; wherein the fiber diameter of the carbon fiber braid is 0.1-10 μm.

8. The preparation method according to claim 1, characterized in that: The specific steps of step S4 include: placing the nano-silicon carbide-conductive substrate composite in a liquid dispersant, using ultrasonic treatment to separate the nano-silicon carbide from the conductive substrate and disperse it in the liquid dispersant; and then removing the liquid dispersant through vacuum drying to obtain nano-silicon carbide particles.

9. The preparation method according to claim 8, characterized in that: In step S4, the ultrasonic treatment time is 10-60 min, the power is 200-1000 W; the vacuum drying temperature is 30-100° C., the time is 10-60 min, and the vacuum degree is 100-1000 Pa.

10. A nano silicon carbide particle, characterized in that: The nano silicon carbide particles are obtained by the preparation method according to any one of claims 1 to 9.